2018
DOI: 10.1371/journal.pone.0197406
|View full text |Cite
|
Sign up to set email alerts
|

Transport of enniatin B and enniatin B1 across the blood-brain barrier and hints for neurotoxic effects in cerebral cells

Abstract: Enniatins are common contaminants of food and feed and belong to the group of the “emerging” mycotoxins, which are produced by various Fusarium species. Although a wide range of toxic effects, like antibacterial, antifungal, insecticidal and cytotoxic properties, have been described in vitro, so far, no cases of mycotoxicosis connected to enniatins in vivo are reported. Among this group of mycotoxins, enniatin B and enniatin B1 are the most prevalent compounds and therefore are present in the human diet. Ennia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…They reported an occurrence of ENs in up to 25% of analyzed samples ( n = 20) at levels from 1.01 to 119.0 µg/Kg, and revealed higher average concentrations of EN A1 (11.1 µg/Kg), EN B (13.0 µg/Kg), and EN B1 (19.0 µg/Kg) in head than in liver (5.1, 12.6, and 5.3 µg/Kg for EN A1, EN B, and EN B1, respectively). Those findings corroborate the ability of ENs to distribute and persist into tissues, and even penetrate different barriers, including the blood-brain barrier, in higher organisms as previously evidenced in the literature [ 80 , 81 ]. However, mycotoxins were not detected in the protein hydrolysates, suggesting that the fish had not been exposed to mycotoxins.…”
Section: Discussionsupporting
confidence: 90%
“…They reported an occurrence of ENs in up to 25% of analyzed samples ( n = 20) at levels from 1.01 to 119.0 µg/Kg, and revealed higher average concentrations of EN A1 (11.1 µg/Kg), EN B (13.0 µg/Kg), and EN B1 (19.0 µg/Kg) in head than in liver (5.1, 12.6, and 5.3 µg/Kg for EN A1, EN B, and EN B1, respectively). Those findings corroborate the ability of ENs to distribute and persist into tissues, and even penetrate different barriers, including the blood-brain barrier, in higher organisms as previously evidenced in the literature [ 80 , 81 ]. However, mycotoxins were not detected in the protein hydrolysates, suggesting that the fish had not been exposed to mycotoxins.…”
Section: Discussionsupporting
confidence: 90%
“…Disruption in the integrity and function of the intestinal epithelial barrier could lead to the enhancement the permeability of the pathogens and toxins, which can enter into the tissues, blood, and lymphatic vessels, and increase the risk of infection in IBD. [ 199 ] It was demonstrated that AhR activation could protect junctional complexes in the intestinal epithelium and mediate cytokine expression. [ 200 ] Likewise, AhR activation in intestinal epithelial cells can protect the stem cell niche and restore the barrier homeostasis, whereas its deficiency promotes inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Other foods, like nuts, spices, fruits, and their by-products can also be contaminated by these fungal metabolites [11]. In terms of toxicity, ENN and BEA have been shown to be toxic to different animals and humans cell types causing apoptosis, mitochondrial damages, and reactive oxygen species (ROS) production [7,8,10,14,15].…”
Section: Introductionmentioning
confidence: 99%